2019
DOI: 10.3906/sag-1604-116
|View full text |Cite
|
Sign up to set email alerts
|

Is nocturnal enuresis a predisposing factor for the overactive bladder?

Abstract: Background/aims: To perform a limited observational study to ascertain whether there is statistical support that nocturnal enuresis (NE) is a predisposing factor in the development of overactive bladder (OAB). Materials and methods: The authors recruited patients diagnosed with OAB over a period of twelve months, and those who declared a history of NE were asked additional questions regarding the features of their NE. Results: A total of 285 patients were diagnosed with overactive bladder, and 98 (34.38%) o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 33 publications
(31 reference statements)
2
2
0
Order By: Relevance
“…Concerning school performance, the current study revealed that the prevalence of NE among primary school children had a significant association with school performance. This association between prevalence of NE and school performance is more or less a similar findings with those obtained from other studies conducted in South of Egypt, Saudi Arabia, India and Nigeria [11,19,21].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Concerning school performance, the current study revealed that the prevalence of NE among primary school children had a significant association with school performance. This association between prevalence of NE and school performance is more or less a similar findings with those obtained from other studies conducted in South of Egypt, Saudi Arabia, India and Nigeria [11,19,21].…”
Section: Discussionsupporting
confidence: 91%
“…The present study reported a significant association between low socioeconomic level and NE prevalence among primary school children. This result was matching with that of other studies carried out in South Egypt and Benha .In addition, other studies conducted in India and Pakistan revealed that prevalence rate of NE is relatively higher in lower socio-economic levels [4,11,16,19].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…A separate study showed that PNE is related to OAB in children [ 22 ]. Research has indicated that one-third of patients with OAB have PNE, which may be due to involuntary detrusor activity in patients with PNE [ 23 ].…”
Section: Discussionmentioning
confidence: 99%